Catholic culture and the impact of pilgrimage on faith an educator's experience - Capets, Mary Rachel (2018)
In 2014, forty-five educators from Catholic schools in the Archdiocese of Sydney embarked on a sacred journey to Rome for the canonisation of Popes John XXIII and John Paul II. The pilgrimage was designed to offer faith formation, professional development and a means of sharing the faith with their school communities upon return. This study seeks to explore the impact of pilgrimage on the faith of the Catholic educator, his or her practice and subsequently the culture of the school. The study adopts a phenomenographically inspired approach to data collection and analysis. Through two phases of interviews it was found that pilgrimage provides a means of encounter with the traditions of the Catholic faith and culture, the practice of daily prayer and an experience of Christian community. The study supports the views of Victor Turner, who claims that it is through an experience of communitas that one reaches liminality, and thus has an experience of transformation or reaffirmation of what one holds dear; and it concludes that pilgrimage provides a creative means of faith formation for lay staff in Catholic schools.
Keywords: Catholic; Communitas; Culture; Education; Faith; Pilgrimage; Saints; Transformation